Influence Learning Model ARIAS and ARIAS Combined Concept maps to Critical Thinking Skills, Cognitive, and Affective - Ismail Ismail (Jurnal Pendidikan Sains, 2013)
Pengaruh Model Pembelajaran ARIAS dan ARIAS Dipadu Peta Konsep terhadap Kemampuan Berpikir Kritis, Kognitif, dan Afektif Abstract: The learning model Assurance, Relevance, Interest, Assessment, and Satisfaction (ARIAS) combined concept maps can enhance critical thinking skills, cognitive, and affective. The study aims to examine the effect of learning model ARIAS, combined ARIAS concept maps and concept maps on the ability of critical thinking, cognitive, and affective. The research data were collected through the test description and observation sheet. The result showed that the average value of critical thinking skills, cognitive and affective for group learning model combined ARIAS Concept maps very well classified category, class learning ARIAS treatment, and treatment classes Concept maps including both categories. Key Words: influence, ARIAS, concept maps, critical thinking, cognitive, and affective Abstrak: Model pembelajaran Assurance, Relevance, Interest, Assessment, dan Satisfaction (ARIAS)  dipadu peta konsep dapat meningkatkan kemampuan berpikir kritis, kognitif, dan afektif. Penelitian bertujuan untuk menguji pengaruh model pembelajaran ARIAS, ARIAS dipadu peta konsep, dan peta konsep terhadap kemampuan berpikir kritis, kognitif, dan afektif. Data penelitian dikumpulkan melalui tes uraian dan lembar observasi. Hasil analisis data menunjukkan bahwa nilai rata-rata kemampuan berpikir kritis, kognitif dan afektif untuk kelompok model pembelajaran ARIAS dipadu Peta Konsep tergolong kategori sangat baik, kelas perlakuan pembelajaran ARIAS, dan kelas perlakuan Peta Konsep termasuk kategori baik.Kata kunci: pengaruh, ARIAS, peta konsep, berpikir kritis, kognitif, afektif